2012
DOI: 10.3892/or.2012.1787
|View full text |Cite
|
Sign up to set email alerts
|

The expression and significance of the enhancer of zeste homolog 2 in lung adenocarcinoma

Abstract: Abstract. Lung adenocarcinoma, with increased incidence in the world, exhibits poor prognosis and is usually resistant to conventional chemotherapy due to drug resistance. The enhancer of zeste homologue 2 (EZH2), a histone methyltransferase, plays a key role in tumorigenesis and cancer development through chromatin remodeling in various types of cancer. However, its potential role in lung adenocarcinoma has not been well defined. In this study, the expression of EZH2 was examined in lung adenocarcinoma tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Rizzo et al observed the EZH2 is overexpressed in ovarian cancer stem cell-like side populations and is associated with drug resistance (29). A similar role for EZH2 has been reported in lung cancer (30). The present study further investigated EZH2 and found that it was downregulated in cisplatin-sensitive ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 80%
“…Rizzo et al observed the EZH2 is overexpressed in ovarian cancer stem cell-like side populations and is associated with drug resistance (29). A similar role for EZH2 has been reported in lung cancer (30). The present study further investigated EZH2 and found that it was downregulated in cisplatin-sensitive ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 80%
“…Higher expression of the PRC2 protein, EZH2, in NSCLC tumor tissue has been associated with worse overall [112, 118, 219] and disease-free survival [112] in several studies[117]. Likewise, BMI-1 expression has also been correlated with poorer patient outcomes [107, 121, 220], and amplification and concordant overexpression of the PcG, PHC3 , has recently been associated with poorer outcomes in NSCLC [221].…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…A number of studies have reported an association between altered expression of a variety of miRNA and sensitivity to gefitinib [236241], erlotinib [242, 243], cisplatin [244–259], and radiotherapy [253, 260265]. Elevated expression of HOTAIR [223] and EZH2 [117] have also each been associated with cisplatin-resistance.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…Like other cancer types, accumulation of several genetic and epigenetic aberrations has been implicated in the initiation and progression of lung cancer. Focusing on the role of histone methyltransferase EZH2 in the pathogenesis of lung cancer, recent evidences suggests that EZH2 over-expression and polycomb mediated H3K27me3 promote malignancy in various lung cancer types including SCLC and NSCLCs, which is commonly associated with poor prognosis (7880). In a recent study, Coe et al found a strong correlation between deregulation of E2F-Rb pathway in 96% SCLC samples and EZH2 over-expression (81).…”
Section: Role Of Ezh2 In Cancer Progressionmentioning
confidence: 99%